Peningkatan Pemahaman Pemasaran Online Pada Remaja Milenial di SMK Tri Ratna – Jakarta Barat - Supriyanto Supriyanto; Rizqy Aziz Basuki (Universitas 17 Agustus 1945 Jakarta, 2023)
It is very important to provide an understanding of social media to the millennial generation as it is today. Even though the average Tri Ratna Vocational School students are already running a business independently, on the other hand it's good for students to be able to use their gadgets to increase sales through online marketing. Through the activities of using smart phone technology, especially in the use of social media applications, it is hoped that it can be a means of increasing understanding of online marketing for millennial youth at Tri Ratna Vocational School - West Jakarta. The method used in this activity is direct counseling in the form of material presentation and application, especially in online marketing science through social media. The results obtained from this activity were an increase in participants' understanding related to online marketing. Another thing that was found was that some participants did not only take advantage of online marketing but used digital financial applications to support their micro businesses.